The Strategy of Palm Oil Plantation Expansion Business in Relation to Environmental Sustainability Issues: Overcoming The Challenges - Handoko Limaho; Sugiarto Sugiarto; Rudy Pramono; Rio Christiawan (Eduvest - Journal of Universal Studies, 2023)
The qualitative study aims to find out the strategy to overcome challenges of palm oil plantation expansion business in relation to environmental sustainability issues. The contribution of palm oil plantation related business has been an essential part in developing the Indonesian economy for decades. With its contribution to Indonesia’s Gross Domestic Product (GDP) surmounting to more than 15 billion USD in terms of export on the year 2020 (GAPKI, 2020), and with more than 40 billion USD in terms of foreign exchange revenue to Indonesia on the year 2021 (Astra, 2021), it is no doubt the importance of Crude Palm Oil (CPO) which is the by-product of palm oil tree (Elaeis guineensis) has the utmost significant contribution to the Indonesian economy. The palm oil plantation has also significant contribution to the livelihood of the Indonesian citizen by providing jobs for more than 16 million people (CNN, 2021) especially when the pandemic Covid-19 era is happening throughout the world, and the industry also increases the social welfare of its farmers by programs that enrich the farmers with its nucleus-plasma program which fosters a partnership between the palm oil plantation companies and its local communities in a profit sharing mechanism that